INTERPRETATION OF PROTAGONIST AND ANTAGONIST IN THE WORKS OF AGATHA CHRISTIE - Niyazova Mokhichekhra Khayatovna; Tohirova Dilsora Davronovna (Web of Journals Publishing, 2024)
Agatha Christie, the renowned British author, is widely celebrated for her mastery of mystery and detective novels. Her captivating narratives and intriguing characters have enthralled readers for decades. A crucial aspect of Christie's writing lies in her intricate portrayal of protagonists and antagonists, who play a vital role in the development of her captivating plots. In this article, we delve into the interpretation of these central figures in Christie's works and explore the complexities of their roles.
Keywords: protagonist, antagonist, narrative, intricacies, quality, justice, skillful.